O pré-escolar no município de Cuiabá: subsídios para um diagnóstico - Silva, Amil Therezinha Oliveira de Assis e (1982)
The present work presents a annalysis of the Brazilian preschool education according to the official proposals and its results untill 1981, defining as focus of interest the State of Mato Grosso and principally the Cuiabá district. It examines the government legislation and plans which define, model or orientate the preschool in a national level, as well as the evaluation of some studies already made. It appreciats the preschool situation within Mato Grosso State and Cuiabá district, grounded in station pertinent to this education modality. It introduces a description and analysis of the results abtained in a research made in Cuiabá, on schools pertaining to the State, for the obtention the from directors, teachers, and preschool students, of informations relatives to the preschool functioning in this district. The study shows that the Government proposal Íor preschool is contradictory, even from its theoretical presupposition and that the results of its establishing corresponds not to a garantee of good perÍormance but an anticipation of the discriminatory procedure in the school. It shows still that the results of the proposal established in Mato Grosso are not at all encouraging, and the Cuiabá preschool could be considered as a elucidative example: it identifies in these schools, an almost shortcoming in material, administrative, technical, and mainly pedagogic materials for attending the proposal 'Compensative Education'. It shows, at last, that a contact with 447 children said 'needed' or 'marginal' can point out the distance between its 'culture' and the school culture that the preschool pretends, in advance, impose to them.